Multi-dimensional evaluation of pain response in low day-age calves to two types of dehorning - Cui, Weiguo; Liu, Mengyu; Gu, Tianyu; Zhao, Shuai; Yin, Guoan (Frontiers in Veterinary Science, 2024)
The objective of this study was to evaluate the behavioral, physiological, and emotional effects of acute dehorning pain in calves using two methods: dehorning cream and dehorning hot-iron.30 Holstein calves aged 4 days were selected for the study. These calves were randomly assigned to two experimental groups based on the method of disbudding: dehorning cream (n=15) and hot-iron dehorning (n=15).Before and after dehorning, we evaluated their physiological indicators of infrared eye temperature, concentrations of substance P, IL-6, cortisol, haptoglobin, as well as emotional state, and pain-related behavioral reactions. Post-dehorning, the duration of lying down decreased significantly in both groups (DI and DC: 0-4h) after dehorning (P<0.05). both groups exhibited increased frequencies of pain-related behaviors such as head shaking (DI: 1-7h, DC:1-6h), ear flicking (DI: 2-7h, DC: 2-7h), head scratching (DI: 2-3h, DC: 1-7h), and top scuffing (DI: 2h, DC: 2-7h) compared to pre-dehorning (P<0.05). The DC group demonstrated a higher frequency of head-shaking, ear-flicking, head-scratching, and top-rubbing behaviors, along with a longer duration of lying down (0-4h), compared to the DI group (P<0.05). Post-dehorning, play behavior reduced significantly in both groups (6-8h) (P<0.05), whereas judgment bias and fear levels showed no significant change (P>0.05). Physiological measures including eye temperature, and blood levels of substance P and IL-6, did not differ significantly between the groups before and after dehorning (P>0.05). However, 48 hours after dehorning, calves in the DC group had significantly higher haptoglobin levels compared to the DI group (P=0.015). Additionally, salivary cortisol levels in the DC group increased significantly at 3.5h and 7h post-dehorning (P=0.018, P=0.043). Both hot-iron and cream dehorning induced pain in calves, as evidenced by increased pain-related behaviors, elevated salivary cortisol, and higher haptoglobin levels, alongside reduced positive behaviors. Notably, these effects were more pronounced in the DC group than in the DI group, suggesting that dehorning hot-iron may be a comparatively less stressful dehorning method for young calves. Moreover, the brief duration of pain response and weaker response to dehorning observed in 13-day-age calves in this study suggests that dehorning at younger ages may be more advisable and warrants further research.